Kreativitas Nyoman Mulyawan dalam Tari Bala di Kabupaten Lampung Tengah - Handayani, Ketut Putri; Pramutomo, R.M.; Dewi, Maharani Lutvinda (Gesture: Jurnal Seni Tari, 2025)
This research reveals the Creativity of Nyoman Mulyawan as the creator of Bala Dance in Central Lampung Regency. Bala dance is one of the works created by Nyoman Mulyawan by collaborating Lampung dance and Balinese dance. The purpose of this research is to reveal the problems: (1) How is the Form of Bala Dance in Central Lampung Regency? (2) How is Nyoman Mulyawan's Creativity in Bala Dance in Central Lampung Regency? The theoretical basis used is the theory of form and choreography in the book Basic Aspects of Group Choreography. This research uses a qualitative method using a choreographic approach. This research stage uses data collection by means of observation, interviews, and literature study. Then all the data is put together and then analyzed, aiming to find out the creativity of bala dance and the results of this research will be described as descriptive text. The results showed that the form of bala dance is a group dance that describes the warrior. In bala dance there are elements that include dance movements, dance music, dance themes, dance makeup, dance clothes, dance types, number of dancers, and dance properties. This creativity is shown from the choreographer, starting from the creation process until the formation of the bala dance.